The Filipino, diaspora and a continuing quest for identity - Aguila, Almond N. (Social Science Diliman, 2015)
Defining Filipinoness has been problematic throughout history. Previous studies have focused on the persistent impact of the colonial experience on Filipinos (Bernad, 1971; Constantino, 1977; Enriquez, 1992; Yacat, 2005). Some scholars have framed their understanding vis-a-vis the search for a national consciousness resulting in a unif ied Filipino identity (Anderson, 1983; Constantino, 1969). But in the age of globalization, statehood and nationhood have become questionable concepts (Adamson & Demetriou, 2007; Ahmad & Eijaz, 2011; Guéhenno, 1995; Omae, 1995). Who has the Filipino become amid a modern-day diaspora? I propose an analysis of history not as archival and disconnected from the present but as part of an ongoing story of identity formation. Recognition is given to kapwa, a view of self-and-other as one. This indigenous ontology offers a postmodern lens to understand the complexities of being Filipino through time and space. For contemporary Filipinos, identity formation may involve a continuing resistance against colonialism now set amid the diaspora in the digital age. This article further presents an alternative view of Filipinoness by arguing that diasporics remain Filipino despite physical estrangement from the Philippines. An essential point echoed from other scholars is how cultural identity should not be seen as singular and unchanging (Hall, 1990; Said, 1993/2012). Rather, Filipinoness may refer to evolving, varied and fluid Filipino identities. This evolution involves a past that folds into the present and impacts the future in locations around the world.